2022
DOI: 10.1101/2022.03.15.484390
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Noninvasive stimulation of the ventromedial prefrontal cortex modulates rationality of human decision-making

Abstract: The framing-effect is a bias that affects decision-making depending on whether the available options are presented with positive or negative connotations. Even when the outcome of two choices is equivalent, people have a strong tendency to avoid the negatively framed option because losses are perceived about twice as salient as gains of the same amount (i.e. loss-aversion). The ventromedial prefrontal cortex (vmPFC) is crucial for rational decision-making, and dysfunctions in this region have been linked to co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Furthermore, we showed that excitatory vmPFC tDCS resulted in less biased and, thus, more rational decision‐making and feedback processing compared to inhibitory stimulation (Kroker et al, 2022). Although in the preceding financial gambling studies we tested stimulation‐driven modulations of rather basic gain versus loss processing (Kroker et al, 2022a, 2022b; Rehbein et al, 2023), it has been proposed that the vmPFC is also involved in higher‐order reward processing (e.g., Hiser & Koenigs, 2018). Therefore, in the present study, we aimed to investigate whether vmPFC tDCS affects more complex or higher‐order feedback evaluation in addition to modulating basic gain versus loss processing.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we showed that excitatory vmPFC tDCS resulted in less biased and, thus, more rational decision‐making and feedback processing compared to inhibitory stimulation (Kroker et al, 2022). Although in the preceding financial gambling studies we tested stimulation‐driven modulations of rather basic gain versus loss processing (Kroker et al, 2022a, 2022b; Rehbein et al, 2023), it has been proposed that the vmPFC is also involved in higher‐order reward processing (e.g., Hiser & Koenigs, 2018). Therefore, in the present study, we aimed to investigate whether vmPFC tDCS affects more complex or higher‐order feedback evaluation in addition to modulating basic gain versus loss processing.…”
Section: Introductionmentioning
confidence: 99%